Resveratrol ameliorates chronic unpredictable mild stress-induced depression-like behavior: involvement of the HPA axis, inflammatory markers, BDNF, and Wnt/β-catenin pathway in rats - Yang X (Dove Medical Press, 2017)
Xin-Hua Yang,1 Su-Qi Song,2 Yun Xu3 1Department of Pharmacy, Hefei Eighth People’s Hospital, Hefei, 2Department of Psychiatry, Chaohu Hospital of Anhui Medical University, Hefei, 3Faculty of Pharmacy, Anhui Medical University, Hefei, China Abstract: Classic antidepressant drugs are modestly effective across the population and most are associated with intolerable side effects. Recently, numerous lines of evidence suggest that resveratrol (RES), a natural polyphenol, possesses beneficial therapeutic activity for depression. The aim of the present study was to explore whether RES exhibits an antidepressant-like effect in a depression model and to explore the possible mechanism. A depression model was established via chronic unpredictable mild stress (CUMS), after which the model rats in the RES and fluoxetine groups received a daily injection of RES or fluoxetine, respectively. The sucrose preference test, open field test, and forced swimming test were used to explore the antidepressant-like effects of RES. The activity of the hypothalamic–pituitary–adrenal (HPA) axis was evaluated by detecting the plasma corticosterone concentration and hypothalamic mRNA expression of corticotrophin-releasing hormone. The plasma interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor-α (TNF-α) concentrations were measured by enzyme-linked immunosorbent assay. Hippocampal protein expression of brain-derived neurotrophic factor (BDNF) and the Wnt/β-catenin pathway were analyzed by western blot. The results showed that RES relieved depression-like behavior of CUMS rats, as indicated by the increased sucrose preference and the decreased immobile time. Rats that received RES treatment exhibited reduced plasma corticosterone levels and corticotrophin-releasing hormone mRNA expression in the hypothalamus, suggesting that the hyperactivity of the HPA axis in CUMS rats was reversed by RES. Moreover, after RES treatment, the rats exhibited increased plasma IL-6, CRP, and TNF-α concentrations. Furthermore, RES treatment upregulated the hippocampal protein levels of BDNF and the relative ratio of p-β-catenin/β-catenin while downregulating the relative ratio of p-GSK-3β/GSK-3β. Our findings suggest that RES improved depressive behavior in CUMS rats by downregulating HPA axis hyperactivity, increasing BDNF expression and plasma IL-6, CRP, and TNF-α concentrations, and regulating the hippocampal Wnt/β-catenin pathway. Keywords: brain-derived neurotrophic factor, chronic unpredictable mild stress, depression, hypothalamus–pituitary–adrenal axis, resveratrol, Wnt/β-catenin pathway, interleukin-6, C-reactive protein, tumor necrosis factor-α